2022
DOI: 10.3390/nu14122497
|View full text |Cite
|
Sign up to set email alerts
|

The Hydration Status of Adult Patients with Oropharyngeal Dysphagia and the Effect of Thickened Fluid Therapy on Fluid Intake and Hydration: Results of Two Parallel Systematic and Scoping Reviews

Abstract: Background: The effect of oropharyngeal dysphagia (OD) and thickened fluid (TF) therapy on hydration status has not been well defined in the literature. We aimed to assess the hydration status in patients with OD and the effect TF therapy has on it. Methods: Two literature reviews following PRISMA methodology (each one including a systematic and a scoping review) were performed: (R1) hydration status in adult patients with OD; (R2) effect of TF therapy on fluid intake and dehydration. Narrative and descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 87 publications
0
12
0
3
Order By: Relevance
“…It is inferred that refusal to drink liquids by some older adults can lead to dehydration problems, impacting their health in general. Caregivers who understand the importance of safe daily water intake for older adults are alert to possible signs of an inadequate supply ( 17 , 18 ) . In this study, an older adult presented restrictions on oral food consistency and refused to drink liquids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is inferred that refusal to drink liquids by some older adults can lead to dehydration problems, impacting their health in general. Caregivers who understand the importance of safe daily water intake for older adults are alert to possible signs of an inadequate supply ( 17 , 18 ) . In this study, an older adult presented restrictions on oral food consistency and refused to drink liquids.…”
Section: Discussionmentioning
confidence: 99%
“…Caregivers had reported that, before hospitalization, there was already this refusal even after trying to taste the water. Not drinking fluids leads to skin dehydration and can affect the brain functioning, leading to confusion, difficulty concentrating and cognitive impairment, as well as causing muscle weakness and dizziness, increasing the risk of falls ( 17 , 18 , 19 , 20 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This clinical trial included 85 patients who were recruited from August 2020 to August 2022 at the Gastrointestinal Physiology Laboratory of the Hospital de Mataró, Consorci Sanitari del Maresme (CSdM), Catalonia, Spain. The study recruitment process was severely delayed due to the COVID-19 pandemic [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…OD is highly prevalent in the acute stroke phase (40–78%), and although improvements can be observed during post-stroke recovery, it becomes a chronic condition in up to half of cases [ 1 , 3 , 4 , 5 ]. Post-stroke OD (PS-OD) impairs the efficacy and safety of swallowing, which causes severe complications such as dehydration, malnutrition, respiratory infection, aspiration pneumonia, hospital readmission and death [ 6 , 7 , 8 , 9 ]. PS-OD leads to a deterioration in the health status of patients, and it is an independent risk factor for longer hospital stay, institutionalisation after hospital discharge, poorer functional capacity and increased mortality 3 months after stroke [ 3 ].…”
Section: Introductionmentioning
confidence: 99%